STRATEGI PENGELOLAAN GREEN HUMAN RESOURCE MANAGAMENT SEBAGAI PENGUATAN IDENTITAS PADA PT DJAWIR MITRA SYANDANA - Fadhil, Achmad Zaki; Rudiatno, Rudiatno (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2025)
This study aims to analyze the management strategy of Green Human Resource Management (Green HRM) as a strengthening of the company's identity in PT Djawir Mitra Syandana. Using a qualitative approach, this study collects data through in-depth interviews with various informants who have direct involvement in the implementation of Green HRM. The technique of determining informants was carried out by purposive sampling, while data analysis used triangulation to increase the validity of the findings. The results of the study show that PT Djawir Mitra Syandana has integrated Green HRM in various aspects of human resource management, including environment-based recruitment, sustainability training, green performance evaluation, and incentive systems for employees who contribute to environmental programs. However, there are several challenges that hinder the implementation of this policy, such as labor resistance to change, budget limitations, and the readiness of technological infrastructure. The conclusion of this study emphasizes that the success of Green HRM is highly dependent on management commitment, employee involvement, and external policy support. With a more systematic and innovative strategy, PT Djawir Mitra Syandana can strengthen its identity as a sustainability-oriented company and increase its competitiveness in the industry.